Father and daughter = Fađir og dóttir = Vater und Tochter / Percy Aldridge Grainger - Grainger, Percy (1882 - 1961) (Schott & Co., 2012)
For solo men's voices (TTTBarB), double mixed chorus (SATBarBarB; SSATBarBarB), and orchestra; without the acc.; includes piano reduction of vocal parts for rehearsal only. --- Caption title. --- At head of title: Settings of dance-folksongs from the Færö Islands, Nr. 1. --- Words also printed as text on p. [4]. --- Pref. in English and German by the composer.